Consistency in the observation of features used to classify duct carcinoma in situ (DCIS) of the breast. Issue 8 (1st August 2000) - Douglas-Jones, A G; Morgan, J M; Appleton, M A C; Attanoos, R L; Caslin, A; Champ, C S; Cotter, M; Dallimore, N S; Dawson, A; Fortt, R W; Griffiths, A P; Hughes, M; et al.
Abstract : Aim— To determine interobserver and intra-observer agreement in the assessment of cytological grade and intraduct necrosis in pure duct carcinoma in situ (DCIS) of the breast. Methods —Sixty unselected cases with illustrated diagnostic criteria were circulated to 19 practising histopathologists. Results —Overall agreement was moderate for cytological grade in three categories: 71% agreement; weighted κ (κw), 0.36; intraduct necrosis in three categories (absent, present, extensive): 76% agreement; κw, 0.57; and the Van Nuys classification system: 73% agreement; κw, 0.48. Agreement was no better among observers participating in the National External Quality Assurance Programme. Intra-observer agreement for cytological assessment (69.6% agreement; κw, 0.52) and intraduct necrosis (68.3% agreement; κw, 0.48) was moderate, suggesting that individual variation rather than precision of criteria contributes to the lack of agreement. Conclusions —Moderate agreement on observations can be achieved by non-specialist pathologists, with better agreement on necrosis than cytological grade. There was evidence of consistent individual bias towards over or under scoring cytological grade, which could be corrected with adequate and prompt feedback.